Does Regional Training Supply Determine Employees' Training Participation? - Katja Görlitz; Sylvi Rzepka (Institute for the Study of Labor (IZA), 2014)
Using data from the National Educational Panel Study of 2009/2010, this paper investigates the relationship between regional training supply and employees' training participation. Controlling for other regional factors such as the local unemployment rate, the educational level, the population density and the regional industry composition, the results indicate that training participation is significantly higher in regions with many firms in the training supply market. The predictive power of the other regional factors is rather minor.
Keywords: J24; R12; 330; training; local labor markets